Analisis Perlindungan Hukum Terhadap Pekerja Wanita Dari Tindakan Diskriminasi Berdasarkan Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenaagakerjaan - Rahmat Darmawan, Rizki; Suryani Hamzah, Any (Private Law, 2024)
The purpose of this research is to determine the legal protection arrangements for female workers based on Law Number 13 of 2003 on Employment and to identify the factors that influence the legal protection for female workers under the same law. The benefits of this study include academic, practical, and theoretical advantages. The research methodology employed a statute approach and a conceptual approach. The legal protection for female workers encompasses various rights, such as the freedom to choose their occupation, reproductive rights, equal wages, and occupational health and safety rights. Factors influencing legal protection for female workers include legal factors, law enforcement factors, legal facility factors, and societal factors.